SOCIAL CAPITAL AND COMMUNITY PARTICIPATION: A CASE STUDY OF GAMPONG BLANG GEULUMPANG - Yunita Arafah; Gadis Afra Zahara; Farisa Sabila (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
This study aims to analyze the influence of social capital on community participation in Gampong Blang Geulumpang, particularly in the development of the Idi Nusantara Fisheries Port (PPN). Social capital components, including trust, norms, and tolerance, are considered vital in enhancing community engagement. A quantitative approach was employed using Structural Equation Modeling (SEM) processed through SmartPLS 4.0 software. Primary data were collected from 86 respondents selected through purposive sampling. The findings suggest that social capital has a significant impact on community participation. Trust and norms are the most contributing elements, while tolerance creates a conducive environment, but has no direct effect on participation. The study recommends strengthening social capital elements, particularly trust and norms, to support active and sustainable participation in development efforts. The results are expected to serve as a reference for policymakers and academics in managing social capital in coastal areas.